AN ultrasound imaging study of the tense-lax distinction in canadian french vowels - Dalton, Will (Canadian Acoustics, 2011)
An ultrasound imaging study of the tense-lax distinction in Canadian French vowels is presented. Advanced tongue root (ATR) vowels are produced with significant tongue root advancement, creating a large pharvngeal resonant cavity that is not present during production of non-advanced vowels. Cross-linguistically, a number of gestural strategies are employed to create a distinction among so-called tense and lax vowels. In Igbo, these vowels differ only in tongue root position, while in Akan and Germanic languages such as English, they differ in both tongue root position and tongue body height. The purpose of this experiment is to determine which articulatory gestures are used to distinguish between tense and lax vowels using ultrasound imaging to directly measure tongue position during speech production of native speakers of CF.